2006
DOI: 10.1007/s00439-006-0252-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of uptake of obesity genetic testing among affected adults

Abstract: Given that a large number of candidate genes coding for a tendency toward obesity have been identified and some findings have been replicated, we explored characteristics of those who would be most likely to obtain future genetic testing for this tendency. During a series of focus groups, obese respondents rated their likelihood of obtaining testing under conditions in which either genetically-targeted drug treatment would be available, a positive test would be associated with a prognosis for developing diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 68 publications
1
12
1
Order By: Relevance
“…In the present analyses, we found that genetic causal beliefs did not affect interest in receiving personal results. This is in contrast to our expectation that participants who attribute complex diseases to genetic factors would report finding more value in receiving personal genomic results, and are also in contrast to the findings of Segal et al (2007a). The relationship between genetic causal beliefs and interest in personal genomic information warrant further investigation.…”
Section: Discussioncontrasting
confidence: 86%
See 4 more Smart Citations
“…In the present analyses, we found that genetic causal beliefs did not affect interest in receiving personal results. This is in contrast to our expectation that participants who attribute complex diseases to genetic factors would report finding more value in receiving personal genomic results, and are also in contrast to the findings of Segal et al (2007a). The relationship between genetic causal beliefs and interest in personal genomic information warrant further investigation.…”
Section: Discussioncontrasting
confidence: 86%
“…Associations between genetic causal beliefs and reactions to personal genetic test results have previously been explored (Cameron et al 2009;Decruyenaere et al 2000;Marteau and Weinman 2006), but with the exception of one focus group study examining interest in genetic testing for obesity among obese adults (Segal et al 2007a), the present study is the first that we are aware of to examine the association between genetic causal beliefs and interest in personal genomic information upstream in the genomic feedback process in an unselected patient population. We previously reported that the majority of participants in this study believed that genetics influences all four diseases "some" to "a lot" (Sanderson et al 2013).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations